Baby Gymnastics Visualization Guide Using Macromedia Dreamweaver 8.0 - Titasari Budianti; Rahayu Noveandini, SKom., MMSI (Jurnal Sistem Informasi, 2007)
This exercise guide visualization using Dreamweaver 8 as an editor in web design. This website explains in infant development, benefits and rules baby gymnastics, and gymnastics movements baby. And on every page there are pictures gymnastic movement and an explanation of the picture.